Long-acting beta2-adrenergic agonist in pediatric and adolescent asthma patients, 2003–2011. (December 2014) - Zhou, Esther H.; Kang, Elizabeth M.; Seymour, Sally; Iyasu, Solomon
Abstract Objectives: To evaluate changes in the dispensing patterns of long-acting beta2-adrenergic agonist (LABA) in pediatric and adolescent asthma patients in relation to multiple Food and Drug Administration (FDA) regulatory activities from 2003 to 2011. Methods: We estimated LABA dispensing to pediatric asthma patients across three periods: 2003–2004 (after the first labeling change), 2005–2009 (after regulatory activities in 2005 and before 2010 LABA labeling change) and 2010–2011 (after 2010 LABA labeling change), using the IMS Health Plan Claims database. We estimated dispensing patterns over time for single-ingredient (SI) LABA and fixed-dose combination (FDC) of inhaled corticosteroid (ICS) and LABA (FDC-ICS/LABA). We also evaluated prior use of non-LABA asthma-control medication (ACM) before LABA initiation. Results: Of the 147 862 pediatric and adolescent asthma patients who initiated a LABA during the entire study period, the majority (96%) were FDC-ICS/LABA initiators. The proportion of SI-LABA among any LABA initiators was small and declined (9%, 4% and 2%, trend test p < 0.001) for the three periods. Among the patients who initiated, the proportions with prior use of an ACM (1–90 days prior) were 35%, 36% and 39% for the three periods. Conclusions: The significant decline in the proportion of SI-LABA initiation over these years is consistent with FDA's recommendations. However, the favorable trend cannot be solely attributed to FDA activities as changes to clinical practice guidelines, and media publicity may have played a role. Investigating the reasons for the low ACM use before LABA initiation may inform approaches to further improve appropriate use of LABA in young asthma patients.